The Effect of Project Based E-Learning Models toward Learning Outcomes and Critical Thinking Skills of Vocational High School Students - Made Delina Rusnawati; I Wayan Santyasa; I Made Tegeh (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2020)
Learning outcomes and critical thinking skills are main competencies that students must achieve in Digital Simulation subjects. This study aimed to describe the differences in learning outcomes and critical thinking skills together between students who learned by using project-based e-learning model and students who learned by using direct e-learning in Digital Simulation subjects. This research used quasi experiment method. The research design used was a pretest-posttest control group design. The research sample consisted of 4 classes or 133 students by using a simple random sampling technique. This study used two test instruments namely, the learning outcomes test in the form of objective tests and the critical thinking skills test in the form of essay test. Data were analyzed descriptively and Multivariate Analysis of Covariate (Mancova) with hypothesis testing using a significance level of 0.05. The findings showed that first, there were differences in learning outcomes and critical thinking skills simultaneously between students who learned by using a project-based e-learning model and students who learned by direct e-learning model. Second, there was no difference in learning outcomes between students who learned by using the project-based e-learning model and students who learn by direct e-learning model. Third, there were differences in critical thinking skills between students who learned by using the project-based e-learning model and students who learned by using direct e-learning model.